A new species of Heilipus Germar (Coleoptera: Curculionidae: Molytinae) associated with commercial species of Annonaceae in Brazil, and comments on other species of the genus causing damage to avocado trees in Brazil - Vanin, Sergio Antonio; Bená, Daniela De Cassia (Zootaxa, 2015)
Heilipus gibbus sp. nov. (type locality: Brazil, state of São Paulo, Angatuba) is described from 73 specimens. The holotype and three paratypes from the same locality were reared from larvae collected in the basis region, near the ground, of an atemoya tree (a hybrid of the sugar-apple, "pinha" or fruta-do-conde"—Annona squamosa L., and the cherymoya, A. cherimoya (Mill.), Annonaceae). Heilipus gibbus sp. nov. can cause severe injury to commercial Annonaceae, and has been misidentified in the collections and the literature as Heilipus catagraphus Germar, 1834. The new species and H. catagraphus have a very similar color pattern, but can be easily distinguished by the rostrum shape in lateral view, being humped in H. gibbus sp. nov. but evenly arcuate in H. catagraphus. Illustrations of habitus and of male and female genitalia are provided to the new species and for avocado stem boring species of Heilipus which occur in Brazil (H. catagraphus and H. rufipes). Comments are made for H. elegans Guérin, 1844, which record to Brazil is probably based on a misidentification.